m/3-1=2m-7

Simple and best practice solution for m/3-1=2m-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m/3-1=2m-7 equation:



m/3-1=2m-7
We move all terms to the left:
m/3-1-(2m-7)=0
We get rid of parentheses
m/3-2m+7-1=0
We multiply all the terms by the denominator
m-2m*3+7*3-1*3=0
We add all the numbers together, and all the variables
m-2m*3+18=0
Wy multiply elements
m-6m+18=0
We add all the numbers together, and all the variables
-5m+18=0
We move all terms containing m to the left, all other terms to the right
-5m=-18
m=-18/-5
m=3+3/5

See similar equations:

| 26/13=r/39 | | 10-2m=-2m+2m | | 6x+2=-2x-6 | | 5=3m-7 | | 28c+17-25c=38 | | X+35=3x+14 | | 75-4^3=y | | 2y=4(×-3)+9 | | 7x²+2=-19 | | 2x+5=3+2(x+1 | | 5n+3n+7=-43 | | -500+115x=2685 | | X+12=0.5(4x+12 | | 17−5x=20+3x | | 1/9y-4=-14 | | 6+2n=n+5+3 | | 9(2x-3)-4(5+3x)-5(4+x)=-3 | | d-10=4 | | 7x²+2=19 | | 17-(12-x)=3+(3-2) | | -2x+7=-8+3x | | -100+20x=1140 | | A+9=6a-6 | | 6x+5=3(2x+1)6x+5=3(2x+1) | | -7x-3x+14=6-2x | | 2z-2=4 | | (8/15)=(10/x) | | 2z–2=4 | | 5/2x-1=2/x+3 | | 8/15=10/x | | -10+x+x-5=7x-5 | | (x^2-6x+8)x(x-8)=0 |

Equations solver categories